PERPINDAHAN HARTA WARISAN DI KECAMATAN KOTO BALINGKA KABUPATEN PASAMAN BARAT PERSPEKTIF HUKUM ISLAM - Mulyadi Mulyadi; Agusrianto Agusrianto (Ensiklopedia Education Review, 2026)
The main problem in this thesis is the transfer of inheritance in Koto Balingka District, West Pasaman Regency, from the perspective of Islamic law. The purpose of this discussion is to find out how the process of transferring inheritance and what the causes and views of Islamic law are on the implementation of the transfer of inheritance in Koto Balingka District, West Pasaman Regency, from the perspective of Islamic law. Balingka, West Pasaman Regency, is more concerned with what parents ordered and also because it helps the family economy and assumes that the rights and obligations of boys and girls are the same. When viewed from the perspective of Islamic law, it is not in accordance with what is in Faroid Science. The solution to solving the problems that occur in the transfer of inheritance in Koto Balingka District, West Pasaman Regency, is that the community should learn more about problems in the distribution of inheritance in order to be able to carry out the distribution of inheritance left by the heirs. And also the scholars in the area should monitor and always provide enlightenment to the community in completing the transfer of inheritance in accordance with the prevailing Faroid science.Keywords: Harta, Warisan, Hukum,Islam.